799. METASTELMA ANEGADENSE. (December 2014) - Goyder, David; Linsky, Jean; Bárrios, Sara; Hamilton, Martin; Woodfield‐Pascoe, Nancy; Clubbe, Colin
Summary Metastelma anegadense is a twining perennial vine endemic to the British Virgin Islands, with its largest populations on the low‐lying coralline island of Anegada. It is vulnerable in all sites to changes in land use for tourism and development, grazing pressures, and to elevated sea levels and more intensive hurricanes which are likely with global climate change. It has been assessed as Critically Endangered, the IUCN's highest level threat of extinction.